Perbedaan Efektifitas Senam Mata dan Akupresur Mata Terhadap Penurunan Gejala Computer Vision Syndrome (CVS) pada Remaja - Litha Atikah Harahap; Oswati Hasanah; Rismadefi Woferst (HEALTH CARE: JURNAL KESEHATAN, 2023)
Abstract Introduction: Computer Vision Syndrome (CVS) is a vision syndrome caused by the excessive use of digital media such as computers, smartphones, and others. Nonpharmacological therapies that can be used to treat CVS symptoms are eye exercises and acupressure. This study aims to determine the difference in the effectiveness of eye exercises and eye acupressure against the decrease in symptoms of Computer Vision Syndrome (CVS) in adolescents. Methods: Research design using quasy experiment with pre-test and post-test design without control group design. The sample used was 44 respondents of MTs Negeri 1 Pekanbaru students, 22 respondents of the eye exercises group, and 22 respondents of the eye acupressure group. Sampling techniques are taken based on inclusion criteria with purposive sampling techniques. The measuring instrument used is an observation sheet using the Computer Vision Syndrome Questionnaire (CVS-Q). The analysis used is univariate analysis and bivariate analysis using t-dependent and t-independent tests. Results: The results of this study showed that there was no difference in the effectiveness of eye exercises and eye acupressure against a decrease in CVS symptoms in adolescents with a p value of 0.184 (p > 0.05). Conclusion: It can be concluded that eye exercises and eye acupressure are equally effective for lowering CVS symptoms in adolescents. This should be a concern for adolescents experiencing CVS symptoms to do eye exercises and eye acupressure as an alternative to non-pharmacological treatment and can be practiced independently. Keywords: adolescents, computer vision syndrome, eye acupressure, eye exercise